Novel Strategies to Prevent Total Parenteral Nutrition‐Induced Gut and Liver Inflammation, and Adverse Metabolic Outcomes. Issue 5 (25th May 2020) - Lucchinetti, Eliana; Lou, Phing‐How; Wawrzyniak, Paulina; Wawrzyniak, Marcin; Scharl, Michael; Holtzhauer, Gregory A.; Krämer, Stefanie D.; Hersberger, Martin; Rogler, Gerhard; Zaugg, Michael
Abstract: Total parenteral nutrition (TPN) is a life‐saving therapy administered to millions of patients. However, it is associated with significant adverse effects, namely liver injury, risk of infections, and metabolic derangements. In this review, the underlying causes of TPN‐associated adverse effects, specifically gut atrophy, dysbiosis of the intestinal microbiome, leakage of the epithelial barrier with bacterial invasion, and inflammation are first described. The role of the bile acid receptors farnesoid X receptor and Takeda G protein‐coupled receptor, of pleiotropic hormones, and growth factors is highlighted, and the mechanisms of insulin resistance, namely the lack of insulinotropic and insulinomimetic signaling of gut‐originating incretins as well as the potentially toxicity of phytosterols and pro‐inflammatory fatty acids mainly released from soybean oil‐based lipid emulsions, are discussed. Finally, novel approaches in the design of next generation lipid delivery systems are proposed. Propositions include modifying the physicochemical properties of lipid emulsions, the use of lipid emulsions generated from sustainable oils with favorable ratios of anti‐inflammatory n‐3 to pro‐inflammatory n‐6 fatty acids, beneficial adjuncts to TPN, and concomitant pharmacotherapies to mitigate TPN‐associated adverse effects. Abstract : This review discusses the mechanisms underlying total parenteral nutrition (TPN)‐associated adverse effects on metabolic hormonal balance, the liver, digestive tract, gut‐associated microbiome, and the immune system. A multi‐modal approach to mitigate and treat TPN‐associated adverse effects by the application of next‐generation lipid delivery systems and the use of innovative pharmacotherapies, including genetically‐engineered microorganisms, is proposed.